Observaciones sobre la distribución espacial de Meloidogyne incognita después de la cosecha en dos plantíos de tabaco burley [Nicotiana tabacum]. - López Ch, R. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Two burley tobacco (Nicotiana tabacum L.) fields (A and B) were sampled inmediately after harvest at Repunta, Perez Makin county, Costa Rica, to perform observations on the spatial distribution of Meloidogyne incognita larvae. In each field, samples were taken horizontally at 5, 10 and 15 cm from the Think, between plants in the same row (between plants) and then in a 90 degrees angle, between plants in adjancent rows (between rows). Vertically, in each of the before mentioned points, samples were taken at 15 cm intervals from the soil surface down to 45 cm deep. Horizontally, in field A the highest densities were found at 5 cm from the trunk; densities decreased as the distance from the trunk increased, not only between plants but between rows as welt In field B the highest densities between plants were located 10 cm from the trunk while between rows the location of the highest densities was irregular. Vertically, densities decreased slightly as sampling depth increased in both fields.